Globalization and Diversification of Interior Decoration Styles and Their Impact on Pakistani Handicrafts - Romana Yasmin Khan; Ren Honggu; Moazzam Abbas; Zhang Jinjao; Yuchen Liu; Yang Xinran; Wang Fang; Misbah Ul Islam (Journal of Visual Art and Design, 2023)
With the gradual advancement of globalization, cultural values and traditional decorative practices as well as people’s lifestyles have changed through digital awareness. This has seriously affected the interior decoration industry and brought challenges to the local handicraft industry. Pakistan’s traditional handicraft is famous in the world, but the flow of imported machine-made products in Pakistan has led to a decline of Pakistan’s handicraft industry. This research investigated which factors are involved in home decoration and to see if these factors are advantageous for the handicraft industry or not. The use of handicraft decoration objects varies among people when they design their houses. Thus, study conducted a survey, which found several factors that Pakistani people emphasize in relation to home decoration. Currently, these factors do not benefit the handicraft industry as people pursue a modern lifestyle and they consider handicraft objects without innovation and design outdated. Interior decoration is seen as a major aspect of traditional Pakistani life and culture, with distinct cultural characteristics. Inspired by the latest way of thinking, an interior design first exists as a concept and is then realized through careful planning. It is meant to evoke a specific mood through the strategic use of color, space, and style. In Pakistan, home accessories are generally and strongly influenced by the current fashion in the end market, with many changes brought about by consumers’ purchasing patterns, designers’ and decorators’ styles, and economic conditions. Keeping up with constantly changing trends is the main challenge faced by the traditional handicraft industry sector. In many cases, craftspeople are disconnected from the end market, which is a challenge for them to be able to profit from their work.